Equidade educacional nos anos iniciais do ensino fundamental e vulnerabilidade social nos territórios do município de São Paulo - Penninck, Renan Brazil (2019)
This research aims to investigate if there was an expansion of educational equity in the early years (1st to 5th) of elementary school in São Paulo and, if so, to verify if there is evidence that the phenomenon also extends to the city locations classified as being of high social vulnerability. Experts have argued that the most appropriate principle of justice to underpin basic education policies is basic equality (CRAHAY, 2000; DUBET, 2009), a principle that, according to Ribeiro (2014b), fits into the perspective of justice as equity proposed by Rawls. According to this perspective, at this stage of schooling, subject to compulsory and subjective law, no student should have a level of knowledge lower than expected by the Government. School inequality in Brazil is high and greatly affects blacks, boys and populations with lower socioeconomic status (ALVES; SOARES; XAVIER, 2016). The literature indicates that the phenomenon of social vulnerability in the territories of large cities affects student performance (ÉRNICA; BATISTA, 2012; RIBEIRO; VÓVIO, 2017) and makes achieving justice as equity more complex (PEREIRA-SILVA, 2016), This is why a look at equity in the city of São Paulo is justified, with special attention to its highly socially vulnerable territories. To respond to the research objectives, this research made use of the quantitative approach with data processing of the National Institute of Educational Studies and Research Anísio Teixeira (Inep), QEdu and São Paulo City Hall. Prova Brasil results were analyzed in the São Paulo municipal network from 2011 to 2015 for the segment of the early years of elementary school. The results of this research indicate that the São Paulo municipal education network has expanded in recent years its ability to generate learning for all, in the early years of elementary school, including children with lower socioeconomic status (SES) and schools. located in highly vulnerable territories. However, students in these territories still continue to gain lower levels of proficiency.